Proses Metakognisi Siswa SMP dalam Menulis Ditinjau dari Gaya Belajar - Indra Asnianto (ELite Journal : International Journal of Education, Language, and Literature, 2019)
This research aims to obtain describe of the metacognition process of junior high school students in writing based on the learning styles. Metacognition is the students knowledge or awareness of his own thought processes and outcomes. Metacognition in this research is seen from planning, monitoring, and evaluation of writing news text and exposition text. The topic of the news text and the exposition texts in this study are natural phenomena, cultural phenomena, and social phenomena, as well as the learning styles used are visual, auditory, and kinesthetic. The type of this research is descriptive with qualitative approach. The results of the research reffered that (1) students with visual learning styles, (2) auditory learning styles, and (3) kinesthetic learning styles use metacognition in planning ie understanding the structure of news text and exposition texts, setting goals before writing, setting strategies before writing, and making basic ideas for ease writing; implementation of the visual learning style of controlling the errors of writing and grammar, carefully expressing ideas according to the structure of the text while students with learning styles; implementation of an auditory learning style that expresses ideas but sometimes does not match the text structure; while the implementation of the kinesthetic auditory learning style is expressing ideas but not in accordance with the text structure; and evaluation is to check back, write, and rearrange the writing. Keywords: Metacognition, Learning Styles, News Text, Exposition Teks